Assessment of Information Technology in Electronic Medical Records Using the Concept Health Technology Assessment at X Jepara Hospital - Novita Ariyanti; Farid Agushybana; Aris Puji Widodo (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Hospitals as health service providers need to study the equipment used in health services, which is called a Health Technology Assessment. This research aims to determine the assessment of electronic medical record information technology using the Health Technology Assessment concept at regional General Hospital X Jepara. This research uses a qualitative method with a descriptive design. The research was conducted at the regional general hospital X Jepara which was carried out from March to June 2023. There were 13 informants in this research with 9 main informants and 3 triangulation informants. Data collection techniques use in-depth interviews, observation, and document study. Data analysis for this research is data reduction, data presentation, and conclusion. The results of this research on the concept of effectiveness can increase productivity, be more efficient, make it very easy to publish patient medical records in summary and detail, and doctors and nurses can easily access patient data by logging in using their password. Patient privacy is also maintained with limited access to open it. Service is fast and can increase satisfaction and improve hospital services from an economic perspective using health technology assessment methods. The characteristic aspect of using electronic medical records is that it makes hospital services easier. The security aspect of patient data is guaranteed because system access can only be accessed by users with an account, and the rights of each user are guaranteed. The management of the regional general hospital will easily use electronic medical records and improve the service and quality of Regional General Hospital X Jepara. Keywords: Electronic medical record, Effectiveness, Economic, Technical characteristic, Security